163 AviPlus®S improves wean to finish performance in pigs. (30th November 2020) - Tugnoli, Benedetta; Piva, Andrea; Grilli, Ester
Abstract: The study evaluated the effect of AviPlus®S, a microencapsulated blend of organic acids and nature identical compounds, fed to piglets from weaning through finishing. Ninety pigs (21 days of age, 6.47 ± 0.27 kg) were assigned to 3 diets (5 pigs/pen, n = 6) for a 22-weeks experimental period in 3 phases: weaning (weeks 1 to 6), growing (weeks 6 to 12), and finishing (weeks 12 to 22). The dietary treatments were: CTR, basal diet; AP1, basal + AviPlus®S at 1 kg/MT (weaning phase) and at 0.25 kg/MT (growing and finishing phase); AP2, basal + AviPlus®S at 2 kg/MT (weaning phase) and at 0.5 kg/MT (growing and finishing phase). Growth performance was recorded for each phase. Data were analyzed with ANOVA and differences considered significant at P< 0.05. In the weaning period, AviPlus®S linearly increased ADG and BW (P= 0.006 and P=0.003, respectively) with AP1 and AP2 pigs being heavier than control pigs by 0.44 and 1.1 kg, respectively, at week 6. Growing phase was not affected by treatments. In the finishing period AP2 had significantly higher ADG and G:F compared to control, while AP1 showed intermediate values (P=0.019 and P=0.005, respectively). Overall during the entire trial, AP2 pigs had the highest ADG and G:F, with the final BW being 5.6 kg higher than control at the end of the cycle (114.9 vs 109.3 kg).In conclusion, the supplementation with AviPlus®S allowed to improve growth performance of pigs throughout a production cycle from weaning to slaughter.